Advanced gastric glandular-endocrine cell carcinoma with 1-year survival after gastrectomy - Matsubayashi, Hiroyuki; Takagaki, Shinichi; Otsubo, Takao; Iiri, Takao; Kobayashi, Yuka; Yokota, Takashi; Shichijo, Kimitoshi; Tada, Tetsuya; Satoh, Keiichi; Iwafuchi, Mitsuya (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2000)
Primary gastric endocrine cell carcinoma (ECC) is extremely rare. In general, when it is advanced, gastric ECC causes extensive ulceration (type 2) and invades or metastasizes to other organs, frequently to the liver and sometimes to the lungs or bones, and carries a poor prognosis. We herein report a 67-year-old man with advanced gastric ECC of extensive-polypoid shape (type 1) but without distant metastasis, who underwent total gastrectomy and treatment with oral tegafur-uracil (UFT), and showed no sign of recurrence 1 year later.